Review of solar-thermal collectors powered autoclave for the sterilization of medical equipment - Jean-Fulbert Ituna-Yudonago; Yuridiana-Rocio Galindo-Luna; Octavio García-Valladares; Roberto Best y Brown; Raman Shankar; Jonathan Ibarra-Bahena (Alexandria Engineering Journal, 2021)
This literature review was based on articles published on different types of solar autoclaves used to sterilize the medical instruments. The present paper analysis the various types of solar thermal technologies and the materials used for manufacture. The operating conditions (temperature and pressure) of steam sterilizer used, the climatic conditions as well as the health center where the prototype was tested and installed were also investigated. It emerged from the revised articles that steam sterilizers are part of the systems in which solar thermal energy was used since the 1970s. Conventional solar thermal technologies were the first to be used in solar autoclave prototypes. Due to the high cost of these collectors, several researchers have invested in the design of new prototypes both solar collectors and sterilizers, based on less expensive materials. It has also observed that solar autoclave can hold a pressure steam of 0.10 MPa keeping the internal temperature at 121–140 °C for about 15–20 min.